Sistem Pendukung Keputusan Pemilihan Mekanik Sepeda Motor Yamaha Alfascorfii Dengan Metode Multi Objective Optimization On The Basis Of Ratio Analysis (MOORA) - Safii, M; Zulhamsyah, Azlan (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2018)
Job performance is one of the needs in a company. The demand for these needs aims to foster consumer confidence in the services provided. In service business activities such as the sale and service of professional motorbikes, mechanical work is needed. In determining the best mechanic, there are many criteria that the mechanic must fulfill. These criteria include efforts to overcome problems, years of service, education and discipline. The selection of the best motorcycle mechanics is done to help improve the mechanical workability to be better than before. To assist with the determination or selection in determining someone who deserves to be the best motorcycle mechanic, a decision support system is needed. In this study a case will be raised which is looking for the best alternative based on the criteria that have been determined by using the Multi Objective Optimization Method On The Base Of Ratio Analysis (MOORA). The research was conducted by looking for weight values for each attribute, then ranking process was carried out which would determine the optimal alternative, namely Yamaha Alfascorfii motorcycle mechanics.